Comparison of hemodynamic effects of propofol or alfaxalone during induction in dogs - Sarotti, Diego; Franci, Paolo; Oricco, Stefano; Rabozzi, Roberto; Lardone, Elena (Frontiers in Veterinary Science, 2024)
This randomized prospective clinical study aimed to compare the hemodynamic effects of propofol and alfaxalone for the induction of anesthesia in dogs. Thirty-one healthy dogs undergoing various procedures in a private referral center were premedicated with intramuscular acepromazine (0.015 mg/kg) and methadone (0.15 mg/kg). They then received 5 mg/kg of propofol over 30 s for induction, followed by a maintenance dose of 25 mg/kg/h (Group P), or 2 mg/kg of alfaxalone over 30 s for induction, followed by a continuous rate infusion of 10 mg/kg/h (Group A). Heart rate (HR), mean arterial pressure (MAP), and the velocity time integral (VTI) of the aortic blood flow using transthoracic echocardiography were measured before anesthetic induction and every 15 s for 180 s. Dogs not adequately anaesthetized for intubation were excluded from the hemodynamic evaluation. Events of hypotension (any MAP value lower than 60 mmHg) were also recorded. Statistical analyses utilized ANOVA for repeated measures, two-way repeated measures ANOVA, paired t-tests, or Wilcoxon signed rank-test as appropriate. Significance was set at p < 0.05. Two dogs in Group P (2/14) and 3 in Group A (3/17) were excluded from the study because the anesthesia plane was too light to allow intubation. Treatment P resulted in a significant decrease in MAP between 45 and 75 s during the induction period, with no significant variation in HR, VTI, and VTI*HR. In treatment A, HR increases between 60 and 105 s, VTI decreases at 150–180 s. Analysis between groups did not show any difference in MAP (p = 0.12), HR (p = 0.10), VTI (p = 0.22) and VTI*HR (p = 0.74). During induction, hypotension was detected in 3/12 (25%) dogs in Group P and 1/14 (8%) in Group A. In healthy premedicated dogs, propofol and alfaxalone induction produce similar hemodynamic variations. Propofol induction results in a short-term reduction in MAP, whereas alfaxalone induction preserves MAP and cardiac output by significantly increasing heart rate.